Developmental changes in myoendothelial gap junction mediated vasodilator activity in the rat saphenous artery - Sandow, Shaun L (Blackwell Science Inc, 2004)
A role for myoendothelial gap junctions (MEGJs) has been proposed in the action of the vasodilator endothelium-derived hyperpolarizing factor (EDHF). EDHF activity varies in disease and during ageing, but little is known of the role of EDHF during development when, in many organ systems, gap junctions are up-regulated. The aims of the present study were therefore to determine whether an up-regulation of heterocellular gap junctional coupling occurs during arterial development and whether this change is reflected functionally through an increased action of EDHF. Results demonstrated that in the saphenous artery of juvenile WKY rats, MEGJs were abundant and application of acetylcholine (ACh) evoked EDHF-mediated hyperpolarization and relaxation in the presence of N(ω)-nitro-l-arginine methyl ester (L-NAME) and indomethacin to inhibit nitric oxide and prostaglandins, respectively. Responses were blocked by a combination of charybdotoxin plus apamin, or 1-[(2-chlorophenyl)diphenylmethyl]-1H-pyrazole (TRAM-34) plus apamin, or by blockade of gap junctions with the connexin (Cx)-mimetic peptides, (43)Gap26, (40)Gap27 and (37,43)Gap27. On the other hand, we found no evidence for the involvement of the putative chemical mediators of EDHF, eicosanoids, L-NAME-insensitive nitric oxide, hydrogen peroxide or potassium ions, since 14,15-epoxyeicosa-5(Z)-enoic acid (14,15-EEZE), hydroxocobalamin, catalase or barium and ouabain were without effect. In contrast, in the adult saphenous artery, MEGJs were rare, EDHF-mediated relaxation was absent and hyperpolarizations were small and unstable. The present study demonstrates that MEGJs and EDHF are up-regulated during arterial development. Furthermore, the data show for the first time that this developmentally regulated EDHF is dependent on direct electrotonic coupling via MEGJs.